Optimizing the Use of Instagram Captions as a Teaching Medium to Enhance Students' Descriptive Writing Skills - Erwin Oktoma; Muhammad Aprianto Budie Nugroho; Yayan Suryana; Mujtaba Jamal (Script Journal: Journal of Linguistics and English Teaching, 2025)
Background: Instagram captions play an important role in digital communication and can be used as an innovative tool in writing instruction. By encouraging creativity and clarity, captions help students practice meaningful writing through a familiar platform. This study aims to examine the implementation of Instagram captions in teaching descriptive texts and assess their impact on students' writing skills and motivation.Methodology:This research employed classroom action research (CAR) design, conducted in two cycles, each consisting of five meetings, with the aim of improving tenth-grade students' descriptive writing skills using Instagram as a teaching media. In the planning phase, lesson plans were developed incorporating Instagram post caption activities. During the implementation phase, students were engaged in writing descriptive texts by creating captions for photos on Instagram. Observations were made throughout the teaching process, with field notes documenting the students' participation and enthusiasm. Data were collected through pre-test and post-test assessments to measure students' writing skills, and qualitative data from observations were analyzed to assess classroom dynamics. Findings:The findings of this research indicate a significant improvement in students' descriptive writing skills after the implementation of Instagram post captions as a teaching media. In the pre-test, the mean score was 75.94, with only 50% of students meeting the minimum achievement criteria (KKM). However, after the intervention, the post-test mean score increased to 80.16, with 100% of students achieving the KKM. This demonstrates a 55.57% improvement in students' writing abilities. Additionally, observations during the lessons revealed that students were more engaged and enthusiastic throughout the process, suggesting that Instagram captions effectively captured their interest and contributed to a more active and interactive classroom environment. Conclusion:In conclusion, the use of Instagram post captions as a teaching media has proven to be an effective strategy for improving students' descriptive writing skills in the tenth grade at SMAN 3 Kuningan. The research demonstrated a significant improvement in students' writing performance, with all students meeting the minimum achievement criteria by the end of the study. The integration of Instagram into the learning process not only enhanced students' writing skills but also increased their engagement and enthusiasm during lessons. Therefore, Instagram post captioning can be considered a valuable and innovative tool for teaching writing, particularly in descriptive text, and can be applied in similar educational settings to foster student creativity and motivation in writing.Originality:This study offers an original approach by utilizing Instagram post captions to improve students' descriptive writing skills, integrating social media as an effective tool in enhancing language learning outcomes.